Low-latency Secure Roaming in V2I Networks - Richa, Cesar Huegel; Frohlich, Antonio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
Secure communication is a key requirement for vehicular networks. However, high mobility and density bring several challenges to the roaming mechanism needed to handover the control of vehicles as they move along the roads. Authentication and key management must take place on the way, with strict timing and safety requirements that are seldom matched by the traditional Internet solutions. Those solutions are usually based on Public Key Infrastructures, use ordinary Internet protocols, and are implemented atop general-purpose operating systems that pose additional security threats. In this paper, we propose an extension of the Trustful Space-Time Protocol to implement a low-latency, secure roaming mechanism capable of handing over trust along roadside gateways using a token-based authentication mechanism that fits within a range of realistic scenarios. We modeled such realistic scenarios in the OMNeT++ simulator, using the Castalia Framework, and demonstrated that our protocol is capable to hand vehicles over among gateways of a large, highly utilized road with a roaming latency less than 14 ms.